2023
DOI: 10.1021/acschemneuro.2c00620
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Sevoflurane Exposure Impairs the Learning and Memory of Rat Offspring via HMGB1-Induced NLRP3/ASC Inflammasome Activation

Abstract: The neurotoxic effects of sevoflurane anesthesia on the immature nervous system have aroused public concern, but the specific effects and mechanism remain poorly understood. Pyroptosis caused by the activation of the NLRP3 inflammasome is pivotal for cell survival and acts as a key player in cognitive impairment. This study was carried out to determine the critical role of the NLRP3 inflammasome and high-mobility group box 1 (HMGB1) in sevoflurane-induced cognitive impairment. On gestational day 20 (G20), 3% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Paclitaxel induces disruption of axonal transport through microtubule stabilization, changes in mitochondrial morphology and function, and inflammatory responses, leading to axonal symmetry damage and loss of nerve fibers, and subsequent neurotoxicity ( Niznansky et al, 2022 ). Increasing studies have suggested that GL could provide neuroprotection in nerve system due to its strong anti-inflammatory, anti-apoptosis, antioxidant and autophagy regulation properties ( Kim et al, 2012 ; Yang et al, 2018 ; Gendy et al, 2023 ; Shan et al, 2023 ). A recent study has shown that GL alleviated paclitaxel-induced neurotoxicity in vitro and in vivo by inhibiting the neuronal uptake mediated by organic anion transport peptides (OATPs), which are the main neuronal transporters of paclitaxel ( Klein et al, 2023 ).…”
Section: Roles Of Gl In Cancer Therapymentioning
confidence: 99%
“…Paclitaxel induces disruption of axonal transport through microtubule stabilization, changes in mitochondrial morphology and function, and inflammatory responses, leading to axonal symmetry damage and loss of nerve fibers, and subsequent neurotoxicity ( Niznansky et al, 2022 ). Increasing studies have suggested that GL could provide neuroprotection in nerve system due to its strong anti-inflammatory, anti-apoptosis, antioxidant and autophagy regulation properties ( Kim et al, 2012 ; Yang et al, 2018 ; Gendy et al, 2023 ; Shan et al, 2023 ). A recent study has shown that GL alleviated paclitaxel-induced neurotoxicity in vitro and in vivo by inhibiting the neuronal uptake mediated by organic anion transport peptides (OATPs), which are the main neuronal transporters of paclitaxel ( Klein et al, 2023 ).…”
Section: Roles Of Gl In Cancer Therapymentioning
confidence: 99%
“…It was reported that NLRP3 inflammasome-mediated pyroptosis directly led to cognitive impairment in PND mice model induced by . NF-κB and HMGB1 induced pyroptosis were also elucidated in PND, NF-κB inhibitor or HMGB1 inhibitor treatment effectively improved PND by significantly inhibiting pyroptosis (Dai et al, 2021;Shan et al, 2023). found that esketamine improved POCD in aged rats and alleviated the pyroptosis of astrocytes after LPS exposure, moreover, an underlying connection between STING/TBK1 signaling pathway and caspase-1-mediated pyroptosis was indicated, which required further research.…”
Section: Perioperative Neurocognitive Disordermentioning
confidence: 98%
“…The mitochondrial protectant dexpramipexole (DPX) could sustain mitochondrial function and inhibit NLRP3/caspase-1 pyroptosis pathway, thus ameliorating neuroinflammation and cognitive impairment in SAE (Zhang et al, 2023). Sevoflurane was reported to activate HMGB1-induced NLRP3/ASC inflammasome, induce pyroptosis, and impair cognitive function in PND (Shan et al, 2023), however, in SAE, sevoflurane could act as protective role. Chen et al (2022) demonstrated that sevoflurane could improve cognitive dysfunction by inhibiting the NLRP3-dependent caspase-1/11-GSDMD pathway, in which SIRT1 played a key role.…”
Section: Sepsis-associated Encephalopathymentioning
confidence: 99%